Implementing Splunk : big data reporting and development for operational intelligence : learn to transform your machine data into valuable IT and business insights with this comprehensive and practical tutorial /: big data reporting and development for operational intelligence : learn to transform your machine data into valuable IT and business insights with this comprehensive and practical tutorial. (2013) - Unknown
No abstract available